“SÓCIO, LÓGICO!” : An experience for the appreciation of Science and Sociology (Simbiótica. Revista Eletrônica, 2024)
The Sócio, Lógico! is a project that aims to promote Science and Sociology, through a profile on the social network Instagram. It is the result of the collective work of coordinating teachers, preceptors and residents participating in the Pedagogical Residency Program (PRP), linked to the degree course in Social Sciences at the State University of Londrina (UEL). The project was designed to play an important role in the training and trajectory of Basic Education students and teachers, consolidating itself as a complementary teaching guide, where themes and debates are presented in an accessible and explanatory way. In this text, the planning and execution stages of the project will be presented, as well as the work methodology used, and the results obtained. The Socio, of course! was born with the purpose of strengthening contact between academic scientific knowledge and that acquired in everyday school life.
Keywords: sociology; scientific divulgation; pedagogical residency; social network